Successful outcomes of dengeu fever in various trimesters during pregnancy - Ma, Saung Oo; San, Thitsa Aung (2018)
Dengue fever is the most common viral infection transmitted worldwide. Currently, the incidence of dengue infection has been increasing among adults including pregnant women. Case reports of dengue fever in pregnancy dramatically increased in Malaysia recently and most of the report cases are from urban area and working and schooling groups are mostly affected. We reported here three interesting cases of dengue fever in pregnancy at different trimesters who had successful maternal and fetal outcomes. We reported the case series of dengue fever in pregnancy at different gestational age. First two cases were occurred at early gestation age (first and second trimester) and successfully treated with supported treatment. However, third case was occurred in third trimester and complicated with compensated shock and superimpose atypical pneumonia. All patients had successful recovery without maternal and fetal complications. From our case series, we found that severity of dengue fever in pregnancy is increased with advanced gestation. More cases of dengue infection in pregnancy can be found because of the increasing incidence of dengue infection among adults. The infection should be suspected when a pregnant woman presents with the similar pattern of symptoms and signs like in a non-pregnant case. Conservative treatment should be given unless there are complications. Successful favourable pergnancy outcome can be achieved with early recognition with correct diagnosis and timely intervention with high index of suspecsion in dengue endemic region.